Allergen immunotherapy and asthma. (3rd February 2020) - Tosca, Maria Angela; Olcese, Roberta; Licari, Amelia; Ciprandi, Giorgio
Abstract: Allergen immunotherapy (AIT) represents at present the unique disease‐modifying treatment strategy for IgE‐mediated allergic diseases. AIT can induce clinical improvement of allergic asthma, including reduced symptoms, medication use, and improvement of quality of life, with a long‐lasting effect after cessation of treatment. Notably, the current asthma guidelines are now recommending sublingual immunotherapy as an add‐on therapy for asthma in adults and adolescents with house dust mite allergy. Clinical indications of AIT, with particular reference to pediatric asthma, mechanisms of clinical and immunological tolerance to allergens, and the potential biomarkers predicting clinical response are discussed.